2021
DOI: 10.36740/wlek202111104
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Mental State of Students in the Process of Online Education During the Coronavirus Pandemic

Abstract: The aim: Exploring the specifics of the underlying mental states of university students in the context of online learning during the COVID-19 pandemic and identifying their relationship to mental health. Materials and methods: The study of mental states was carried out using three valid methods, namely: a clinical questionnaire for the detection and evaluation of neurotic states (K. Yakhin, D. Mendelevich), a questionnaire for diagnosing the level of social frustration (L. Wasserman, adaptation of V. Bojko), S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For example, low quality of life and a higher frequency of depression and/or anxiety were observed in university students while online learning [14]. During the COVID-19 restriction period, they are forced to stay in a closed environment to attend classes for several hours each day and lack direct social connections [15]. Online learning platforms have also increased the duration of computer, tablet, and smartphone usage, the study load and volume of tasks and assignments, leading to lack of sleep, and destructive eating behaviors [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, low quality of life and a higher frequency of depression and/or anxiety were observed in university students while online learning [14]. During the COVID-19 restriction period, they are forced to stay in a closed environment to attend classes for several hours each day and lack direct social connections [15]. Online learning platforms have also increased the duration of computer, tablet, and smartphone usage, the study load and volume of tasks and assignments, leading to lack of sleep, and destructive eating behaviors [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 restriction period, they are forced to stay in a closed environment to attend classes for several hours each day and lack direct social connections [15]. Online learning platforms have also increased the duration of computer, tablet, and smartphone usage, the study load and volume of tasks and assignments, leading to lack of sleep, and destructive eating behaviors [15,16]. Moreover, online learning during the COVID-19 pandemic resulted in changes in food intake and lifestyle habits, including increased consumption of unhealthy diets such as sugary beverages, snacks, and sweets and decreased physical activity and exercise [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Borisenko et al observed similar findings as they described the change from in-person to online teaching to significantly impact students' mental health. Students were found to experience increased anxiety and depression [20]. Studies conducted during the COVID-19 pandemic showed young people to be especially vulnerable to increased psychological stress, probably due to a stronger need for social interactions, with young women seeming to be more vulnerable than young men to mental health problems [21].…”
Section: Discussionmentioning
confidence: 99%